Dynamic Response of Bottom-Sitting Steel Shell Structures Subjected to Underwater Shock Waves - Fantong Lin; Xianxiang Zhou; Lan Xiao; Ziye Liu; Chaojia Liu (Infrastructures, 2025)
This study examines the dynamic response of bottom-sitting steel shell structures subjected to underwater shock waves. A computational framework integrating the Arbitrary Lagrangian Eulerian (ALE) method was implemented in finite-element analysis to simulate three-dimensional interactions between shock waves and curved shell geometries (hemispherical and cylindrical configurations). An analysis of the impacts of shock-wave propagation media, explosive distance, charge equivalence, hydrostatic pressure, and shell thickness on the dynamic response of these bottom-sitting shell structures is conducted. The findings reveal that the deformation of semi-spherical steel shells subjected to underwater shock waves is significantly greater than that of shells subjected to air shock waves, with effective stress reaching up to 831.4 MPa underwater. The mechanical deformation of curved steel shells exhibits a gradual increase with increasing explosive equivalents. The center displacement of the hemispherical shell at 800 kg equivalent is 6 times that at 50 kg equivalent. Within the range of 0 to 2.0092 MPa, hydrostatic pressure leads to an approximate 26.34% increase in the center vertical displacement of the semi-cylindrical shell compared with 0 MPa, while restricting horizontal convex deformation. Increasing thickness from 0.025 m to 0.05 m results in a reduction of approximately 60% in the center vertical displacement of the semi-cylindrical shell. These quantitative correlations provide critical benchmarks for enhancing the blast resilience of underwater foundation systems.